-3(6x-1)+12x-14=-30.2

Simple and best practice solution for -3(6x-1)+12x-14=-30.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6x-1)+12x-14=-30.2 equation:


Simplifying
-3(6x + -1) + 12x + -14 = -30.2

Reorder the terms:
-3(-1 + 6x) + 12x + -14 = -30.2
(-1 * -3 + 6x * -3) + 12x + -14 = -30.2
(3 + -18x) + 12x + -14 = -30.2

Reorder the terms:
3 + -14 + -18x + 12x = -30.2

Combine like terms: 3 + -14 = -11
-11 + -18x + 12x = -30.2

Combine like terms: -18x + 12x = -6x
-11 + -6x = -30.2

Solving
-11 + -6x = -30.2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + -6x = -30.2 + 11

Combine like terms: -11 + 11 = 0
0 + -6x = -30.2 + 11
-6x = -30.2 + 11

Combine like terms: -30.2 + 11 = -19.2
-6x = -19.2

Divide each side by '-6'.
x = 3.2

Simplifying
x = 3.2

See similar equations:

| 3x-28=-33+2x | | 6x(4yx)=(4+5)4y | | 5x-2(x-3)=15 | | 3x^5-13x^3+12x=f(x) | | 8x=3*4x | | X+9=(-21) | | 6+6(2+-1)=3+12x | | 8n-23=-19+4n | | 30x-5y=90 | | 9.408/-2.45= | | 6(x-4)=-54 | | 34-4x=22 | | 3ln(3x)=0 | | 138-300= | | 3(ln(3x))=0 | | 104/72 | | -5-10y=20 | | 16=y-8x | | -10z-21=-19 | | 132=3k-6(4+7k) | | 3/4(1/2) | | .99n=c | | -5+17f= | | 3y+0=-5 | | -6d+2-7+2d= | | 2x^4-4x^3-x^2+16x=12 | | -10=K(2) | | x=100+1.65(10) | | N-5=-22 | | 6+2a=-26 | | 18-3y=18 | | 2.5x-4.5x=-12.3-3.7 |

Equations solver categories